Lobulated intradermal nevus: A rare entity - Madhulika A Mhatre; Venkataram N Mysore (Indian Journal of Dermatopathology and Diagnostic Dermatology, 2014)
Lobulated intradermal nevus is a rare entity characterized clinically by a yellowish lobulated growth and histologically by fat cell infiltration amidst nests of nevus cells in dermis with evidence of dermal fibrosis. This condition can be confused with a regressing intradermal nevus showing fatty changes, which are typically encountered in elderly individuals. We hereby present a case of lobulated intradermal nevus in a 30-year-old female patient. To the best of our knowledge, this is the first case of its kind to be reported from India.